Lead and cadmium contamination in sediments and blue crabs Callinectes danae from a Ramsar wetland in southeastern Brazil - Araujo, G. S. [UNESP]; Bordon, I. C. [UNESP]; Cruz, A. C.F. [UNESP]; Gusso-Choueri, P. K. [UNESP]; Favaro, D. I.T.; Rocha, R. C.C.; Saint'pierre, T. D.; Hauser-Davis, R. A.; Santelli, R. E.; Braz, B.; Freire, A. S.; Machado, W. T.V.; et al. (My University, 2021)
The Cananéia-Iguape-Peruibe Environmental Protection Area (APA-CIP), on the southeastern coast of Brazil has been designated as a Ramsar wetland site. This estuary is impacted by inputs of contaminated water and sediments from the Ribeira de Iguape River (RIR), in Sao Paulo state. Inputs of metals are mostly from historical mining and metallurgy activities in the RIR watershed. This study aimed to evaluate the concentrations of Pb and Cd in the soft tissues of blue crabs (Callinectes danae) from the APA-CIP, and to determine if the levels of these metals in crab tissues are correlated with the concentrations of these metals in sediments from the estuary. Sediments and crabs were collected during the rainy (March) and dry (September) seasons. Pb concentrations in sediments at two stations in the estuary exceeded sediment quality guidelines, at concentrations of 13.08 and 40.24 µg.g-1 dry weight, respectively. Despite these high Pb concentrations in sediments, the levels of Pb in gill and hepatopancreas tissues of the crabs were relatively low. Cd concentrations in sediments from the estuary were relatively low, but the concentrations in crab tissues were elevated. For instance, the Cd concentrations in the hepatopancreas of crabs collected in the March survey at two stations were 21.73 and 4.24 µg.g-1, respectively. These findings indicate that C. danae may rapidly depurate Pb, while these crabs may rapidly accumulate and poorly depurate Cd. There was some indication that the concentrations of Cd in the hepatopancreas of C. danae were correlated with sediment concentrations, but factors such as varying sand and mud contents of the sediments, and the potential for migration of the crabs within the estuary may constitute confounding factors. These data indicate that governmental action is required to control contamination of this World Heritage Site.
Contaminação de chumbo e cadmio em sedimentos e siris Callinectes danae provenientes de uma Zona Úmida de Importância Internacional Ramsar no sudeste do Brasil.
Keywords: bioaccumulation; bioacumulação; contaminação por metais; crustaceans; crustáceos; Marine Protected Area; metal contamination; Ramsar site; Área Marinha Protegida; área Ramsar